Evidence for the Role of Magnetic Source Imaging in the Presurgical Evaluation of Refractory Epilepsy Patients - Carrette, Evelien; Stefan, Hermann (Frontiers in Neurology, 2019)
The advantages of Magnetoencephalography (MEG) in the field of epilepsy are multiple; just like electroencephalography (EEG), MEG is able to non-invasively measure the epilepsy specific information (i.e. the brain activity reflecting seizures and/or interictal epileptiform discharges) directly and independent of blood flow with a very high temporal resolution in the order of milliseconds. Thanks to its unique sensitivity to tangential sources it gives the full picture when combined with EEG. It allows accurate source imaging of focal epileptic activity and functional cortex and shows a high sensitivity for neocortical sources. In this paper the current evidence and practice for using magnetic source imaging of focal interictal and ictal epileptic activity during the presurgical evaluation of drug resistant patients is being reviewed.